Climate reconstruction during the Last Glacial Maximum based on a marine sediment core from Vestnesa Ridge, Svalbard - Matteis, Felix (UiT Norges arktiske universitet, 2018)
The sediment core HH15-1255PC has been analyzed to reconstruct the climate in the Fram Strait during the last 45,000 years. The coring site is located west of Svalbard on the Vestnesa Ridge, a contourite drift with a high-resolution sedimentary record (Plaza-Faverola et al., 2015). This ridge also includes a pockmark field formed by methane seepage (Vogt et al., 1994). The core HH15-1255PC is a piston core, which was taken in the year 2015 at a water depth of 1,206 m. Onboard the magnetic susceptibility was measured and the core with its total length of 819 cm was cut into 9 sections. In the laboratory of the University of Tromsø different measurements were done on the sediment core before parts of it were analyzed with destructible methods. These methods include core description, x-ray scans, XRF-core scanner, multi-sensor core logger and distribution analyses of foraminifera species. Additionally, the oxygen/carbon isotopes were measured and five samples were used for radiocarbon dating. With the dating results, an age model was constructed by correlating the results with the core JM03-373PC2 described by Jessen et al. (2010). A debris flow deposit, which could be seen in both cores, gave an additional age mark. By comparing the density curve for planktic foraminifera with the δ18O results of the Greenland ice core, Dansgaard-Oeschger event 2 to 11 could correlated. As well, the curves for the detrital carbonate of the Deep Sea Drilling Project have been used and were compared with the 500 μm IRD fraction of the HH15-1255PC core to correlate Heinrich event 2, 3 and 4. The results were put in relation with Dansgaard-Oeschger and Heinrich events and by analyzing the foraminifera distribution, it is possible to see how the influence of different water masses was changing during those events.